2008
DOI: 10.1080/10715760701765616
|View full text |Cite
|
Sign up to set email alerts
|

APE1/Ref-1 regulates PTEN expression mediated by Egr-1

Abstract: APE1/Ref-1, the mammalian ortholog of E. coli Xth, and a multifunctional protein possessing both DNA repair and transcriptional regulatory activities, has dual role in controlling cellular response to oxidative stress. It is rate-limiting in repair of oxidative DNA damage including strand breaks and also has co-transcriptional activity by modulating genes expression directly regulated by Egr-1 and p53 transcription factors. PTEN, a phosphoinositide phosphatase, acts as an 'off' switch in the PI-3 kinase/Akt si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 55 publications
(73 citation statements)
references
References 43 publications
(88 reference statements)
2
71
0
Order By: Relevance
“…expression loss in our resistant sublines. The expression of PTEN has also been reported to be regulated by the EGR1 transcription factor, and three EGR1-binding sites have been identified in the PTEN gene promoter (29,30,43). In this study, we showed a close correlation between PTEN expression and EGR1 expression in drug-resistant PC-9/GEF cells, suggesting that the nuclear translocation of EGR1 directly regulates the expression of PTEN: EGR1 activates transcription of the PTEN gene through binding to its consensus motif in the promoter (44).…”
Section: Discussionmentioning
confidence: 99%
“…expression loss in our resistant sublines. The expression of PTEN has also been reported to be regulated by the EGR1 transcription factor, and three EGR1-binding sites have been identified in the PTEN gene promoter (29,30,43). In this study, we showed a close correlation between PTEN expression and EGR1 expression in drug-resistant PC-9/GEF cells, suggesting that the nuclear translocation of EGR1 directly regulates the expression of PTEN: EGR1 activates transcription of the PTEN gene through binding to its consensus motif in the promoter (44).…”
Section: Discussionmentioning
confidence: 99%
“…Through the redoxmediated activation of NF-ĸB and Hif1α, for example, APE1 indirectly drives IL-8 and VEGF expression, respectively, thus acting as a key regulator of inflammatory and tumor-associated neo-angiogenesis processes. Moreover, APE1 has been implicated in chemoresistance, considering its ability to stimulate the expression of the multi-drug resistance gene MDR1 through the interaction with Y-box-binding protein 1 (YB-1) [53], and its regulatory abilities on the PTEN tumor suppressor [54,55]. We recently characterized a direct role of APE1 in the transcription of SIRT1 gene through the binding of nCaRE-sequences present on its promoter, demonstrating that BER-mediated DNA repair promotes the initiation of transcription of SIRT1 gene upon oxidative DNA damage [41].…”
Section: Unusual Involvement Of Ber Enzymes In the Regulation Of Genementioning
confidence: 99%
“…Ape1 was originally identified as a DNA repair enzyme with apurinic and apyrimidinic endonuclease activity in the base excision repair pathway (Bhakat et al, 2009;. The redox state of cysteine residues in the DNA-binding domain of several transcription factors, such as Erg-1 (Fantini et al, 2008), HIF-1a (Huang et al, 1996), p53 (Gaiddon et al, 1999) and nuclear factor (NF)-kB p50 subunit (Nishi et al, 2002;Ando et al, 2008), has been shown to affect DNA binding. NF-kB is a transcription factor important for the expression of numerous genes contributing to inflammation, and innate and adaptive immune responses (Aggarwal, 2004;Karin, 2006).…”
Section: Introductionmentioning
confidence: 99%